Mechanistic Drivers of Reemergence of Anthropogenic Carbon in the Equatorial Pacific. Issue 18 (22nd September 2017) - Zhai, Ping; Rodgers, Keith B.; Griffies, Stephen M.; Slater, Richard D.; Iudicone, Daniele; Sarmiento, Jorge L.; Resplandy, Laure
Abstract: Relatively rapid reemergence of anthropogenic carbon (Cant ) in the Equatorial Pacific is of potential importance for its impact on the carbonate buffering capacity of surface seawater and thereby impeding the ocean's ability to further absorb Cant from the atmosphere. We explore the mechanisms sustaining Cant reemergence (upwelling) from the thermocline to surface layers by applying water mass transformation diagnostics to a global ocean/sea ice/biogeochemistry model. We find that the upwelling rate of Cant (0.4 PgC yr −1 ) from the thermocline to the surface layer is almost twice as large as air‐sea Cant fluxes (0.203 PgC yr −1 ). The upwelling of Cant from the thermocline to the surface layer can be understood as a two‐step process: The first being due to diapycnal diffusive transformation fluxes and the second due to surface buoyancy fluxes. We also find that this reemergence of Cant decreases dramatically during the 1982/1983 and 1997/1998 El Niño events. Key Points: The upwelling rate of anthropogenic carbon from the thermocline to the surface layer is almost twice as large as air‐sea fluxes Diffusion has a major impact on reemergence of anthropogenic carbon in the Equatorial Pacific Reemergence of anthropogenic carbon decreases dramatically during the El Niño events